2020
DOI: 10.1177/0022022120920720
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-Based Intervention for Individuals With Social Anxiety and Different Levels of Taijin Kyofusho in China

Abstract: The aim of the present study is to investigate the efficacy of internet-based cognitive behavior therapy (ICBT) for individuals with social anxiety (SA) and different levels of Taijin Kyofusho (TKS) in China. The ICBT program was translated into Chinese with some specific contents adapted for Chinese culture. Participants ( N = 80) with SA were assigned either to a treatment ( n = 55) or control group ( n = 25). Both groups were further divided into subgroups, based on their Taijin Kyofusho Scale (TKSS) scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Design and aesthetics Adjust illustrations Illustrate a logo designed by natives 129 User interface Colour schemes were made brighter to be more reminiscent of the Japanese anime aesthetic 85 14. Guidance Person used as guide Guidance by a Chinese therapist 81 , 106 Format of guidance (tailored feedback) Participants can ask for personal contact in addition to automatic feedback 137 Amount of guidance Choice of time of contact 69 , 89 Procedural components 15. Methods used to obtain information Personal interaction (focus groups, interviews, discussions, think aloud) Gain feedback in with qualitative data for the process evaluation and further implementation of the programme 80 Surveys/questionnaires Assessed acceptance and effectiveness 126 Pilot/feasibility studies Feasibility study with Columbian college students 73 , 138 16.…”
Section: Resultsmentioning
confidence: 99%
“…Design and aesthetics Adjust illustrations Illustrate a logo designed by natives 129 User interface Colour schemes were made brighter to be more reminiscent of the Japanese anime aesthetic 85 14. Guidance Person used as guide Guidance by a Chinese therapist 81 , 106 Format of guidance (tailored feedback) Participants can ask for personal contact in addition to automatic feedback 137 Amount of guidance Choice of time of contact 69 , 89 Procedural components 15. Methods used to obtain information Personal interaction (focus groups, interviews, discussions, think aloud) Gain feedback in with qualitative data for the process evaluation and further implementation of the programme 80 Surveys/questionnaires Assessed acceptance and effectiveness 126 Pilot/feasibility studies Feasibility study with Columbian college students 73 , 138 16.…”
Section: Resultsmentioning
confidence: 99%
“…The internet-based self-help program (Shyne) is based on the well-established cognitive-behavioral treatment for social anxiety disorder by Clark and Wells (1995) . It has been proven efficacious in previous studies in our research hub ( Berger et al, 2009 , Berger et al, 2011 ; Schulz et al, 2016 ; Stolz et al, 2018 ) as well as in previous studies from other universities and countries (e.g., Boettcher et al, 2012 ; Chen et al, 2020 ; Kählke et al, 2019 ; Kishimoto et al, 2016 ; Lin et al, 2020 ). The Shyne program consists of the following four treatment components: Psychoeducation : This treatment module delivers (1) detailed evidence-based information on SAD with a focus on maintaining processes (e.g., the vicious cycle of negative thoughts and emotions, cognitions, and behaviors associated with the maintenance of SAD) and (2) a brief overview of the evidence-based CBT strategies to overcome SAD (i.e., psychoeducation about the principles behind cognitive restructuring, attention training and exposure).…”
Section: Methodsmentioning
confidence: 52%
“…Ten studies investigated the effectiveness of internet-based programmes for people with anxiety, depression, trauma, and ADHD. Two RCTs (Lin et al, 2020 ; Wang et al, 2020 ) and two non-RCTs (Chen et al, 2020 ; Kishimoto et al, 2016 ) tested internet-based cognitive behavioural therapy (ICBT) for social anxiety. All four studies showed ICBT reduced the severity of social anxiety, with up to 42% of participants in one study (compared to 20% of participants in the control group; Lin et al, 2020 ) showing significant improvements in social anxiety symptoms post-treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs (Lin et al, 2020 ; Wang et al, 2020 ) and two non-RCTs (Chen et al, 2020 ; Kishimoto et al, 2016 ) tested internet-based cognitive behavioural therapy (ICBT) for social anxiety. All four studies showed ICBT reduced the severity of social anxiety, with up to 42% of participants in one study (compared to 20% of participants in the control group; Lin et al, 2020 ) showing significant improvements in social anxiety symptoms post-treatment. Lin et al ( 2020 ) also evaluated the effects of internet-based programmes on cultural specific condition, Taijin Kyofusho (TKS), which is a culture-related subtype of social anxiety recognised by both the DSM-5 and the ICD-10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation